Gereja Nasara Nasathirah di Fansur Abad ke-7: Sebuah Catatan untuk Pater Y. Bakker, SJ - Antonius Tukiran (Sekolah Tinggi Filsafat Seminari Pineleng, 2021)
Shaykh Abu Salih the Armenian reported that in the VII century there was a Nasara Nasathirah (Nestorian) Church in Fansur or Fahsur. According to Y. Bakker, Fansur or Fahsur is the name of a country in North Sumatra and the Nestorian Church is the Catholic Church. Y. Bakker’s interpretation is somewhat weak for two reasons. First, Fansur or Fahsur can also refer to a country in northwest India. Second, in the seventh century of our era there was not yet section of the Nestorian Church which was in full communion with Rome; thus the Nasara Nasathirah Church cannot be called a Catholic Church if the Catholic Church is understood as a Church that is in full communion with the Roman Church. However, the Nasara Nasathirah Church can be called a Catholic Church if the Catholic Church means the Church which based herself on the faith in Jesus Christ